Trauma and Paralysis in Arthur Miller's Plays - Moravcová, Diana (Univerzita Pardubice, 2025)
This bachelor's thesis explores the representation of trauma and paralysis in three selected plays by Arthur Miller (After the Fall, Broken Glass, and Resurrection Blues). Drawing on literary trauma theory, the study investigates how these concepts are expressed through dramatic structure, character development, and language. Particular attention is given to the personal, collective, and cultural dimensions of trauma and paralysis, as well as their impact on identity, interpersonal relationships, and ethical agency. The analytical part of the thesis is preceded by a theoretical section that defines the key terms and places the plays within their broader historical and cultural context.
Trauma a paralýza ve vybraných hrách Arthura Millera
Keywords: trauma; paralýza; Miller, Arthur; americké drama; Židé; trauma; paralysis; Miller, Arthur; American drama; Jews